FIFA – Fast Interpolation and Filtering Algorithm for Calculating Dyadic Green's Function in the Electromagnetic Scattering of Multi-Layered Structures (Communications in Computational Physics, 2018)
The dyadic Green's function in multi-layer structures for Maxwell equationsis a key component for the integral equation method, but time consuming to calculate.A novel algorithm, the Fast Interpolation and Filtering Algorithm (FIFA), for the calculationof the dyadic Green's function in multi-layer structures is proposed in thispaper. We discuss in specific details, ready for use in practical calculations of scatteringin layer media, how to apply FIFA to calculate various components of the dyadicGreen's function. The algorithm is based on two techniques: interpolation of Green'sfunction both in the spectral domain and spatial domain, and low pass filter windowbased acceleration. Compared to the popular Complex Image Method (CIM), FIFAprovides the same speed and overcomes several difficulties associated with CIM whilebeing more general and robust. Specifically, there are no limitations on the frequencyrange, the number of layers in the structure and the type of Green's functions to becalculated, and moreover, no need to extract surface wave poles from the spectral formof the Green's function. Numerical results are given to demonstrate the efficiency androbustness of the proposed method.